An Ontological Approach to Elicit Safety Requirements - Provenzano, Luciana; Hanninen, Kaj; Zhou, Jiale; Lundqvist, Kristina (2017 24th Asia Pacific Software Engineering Conference (APSEC), 2017)
Safety requirements describe risk mitigations against failures that may cause catastrophic consequences on human life, environment and facilities. To be able to implement the correct risk mitigations, it is fundamental that safety requirements are defined based on the results issued from the safety analysis. In this paper, we introduce a heuristic approach to elicit safety requirements based on the knowledge about hazard's causes, hazard's sources and hazard's consequences (i.e. hazard's components) acquired during the safety analysis. The proposed approach is based on a Hazard Ontology that is used to structure the knowledge about the hazards identified during the safety analysis in order to make it available and accessible for requirements elicitation. We describe how this information can be used to elicit safety requirements, and provide a guidance to derive the safety requirements which are appropriate to deal with the hazards they mitigate.